2017
DOI: 10.1007/s10103-017-2155-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irradiation by a novel CO2 9.3-μm short-pulsed laser on sealant bond strength

Abstract: The objective of this in vitro study was to evaluate whether irradiation of enamel with a novel CO 9.3-μm short-pulsed laser using energies that enhance caries resistance influences the shear bond strength of composite resin sealants to the irradiated enamel. Seventy bovine and 240 human enamel samples were irradiated with a 9.3-μm carbon dioxide laser (Solea, Convergent Dental, Inc., Natick, MA) with four different laser energies known to enhance caries resistance or ablate enamel (pulse duration from 3 μs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Differences of the fissure morphologies are visualized in Figure 1 . Long-term success of the resin-based materials might also be influenced by the use of a bonding system [ 10 , 48 , 49 ] and various pretreatment strategies such as laser irradiation [ 50 ], air abrasion of the tooth surface [ 51 ], or preheating of the sealing material [ 52 ].…”
Section: Materials For Sealing Pits and Fissuresmentioning
confidence: 99%
“…Differences of the fissure morphologies are visualized in Figure 1 . Long-term success of the resin-based materials might also be influenced by the use of a bonding system [ 10 , 48 , 49 ] and various pretreatment strategies such as laser irradiation [ 50 ], air abrasion of the tooth surface [ 51 ], or preheating of the sealing material [ 52 ].…”
Section: Materials For Sealing Pits and Fissuresmentioning
confidence: 99%
“…In contrast, other studies have reported enhanced bond strength or no effect on enamel bond strength with the use of laser technology. 46,47 This is possibly because of the use of different energy levels and application modes.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-ablative irradiation on an enamel surface before etch-and-rinse could increase the shear bond strength of composite resin to enamel. 38 However, compared to etch-and-rinse, ablative irradiation before etching cannot enhance shear bond strength of enamel to resin. [38][39][40] The high irradiation energy causes thermal damage to enamel.…”
Section: Enhancing Resin Bonding To Enamelmentioning
confidence: 99%
“…38 However, compared to etch-and-rinse, ablative irradiation before etching cannot enhance shear bond strength of enamel to resin. [38][39][40] The high irradiation energy causes thermal damage to enamel. Large white asperities can be formed on the enamel surface when ablated with high energy.…”
Section: Enhancing Resin Bonding To Enamelmentioning
confidence: 99%